2017
DOI: 10.1016/j.ypmed.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Smoking selectivity among Mexican immigrants to the United States using binational data, 1999–2012

Abstract: Mexican immigrants have lower smoking rates than US-born Mexicans, which some scholars attribute to health selection-that individuals who migrate are healthier and have better health behaviors than their non-migrant counterparts. Few studies have examined smoking selectivity using binational data and none have assessed whether selectivity remains constant over time. This study combined binational data from the US and Mexico to examine: 1) the extent to which recent Mexican immigrants (<10years) in the US are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Importantly, our results are suggestive that cohort effects may be a non-trivial source of bias in cross-sectional studies that examine the relationship between duration of residence and health; future studies should use methods that assess arrival cohort effects. Considering the changing tobacco contexts in immigrants’ origin countries, smoking prevention and cessation interventions should take into account not only time in the US, but also the period during which immigrant cohorts arrived in the US, as well as the smoking trends in immigrants’ origin countries [34,35,36], particularly at the time the immigrant cohort left. For instance, if an immigrant arrives in the U.S. at a time when smoking is already low, the decrease in smoking may be lower in magnitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our results are suggestive that cohort effects may be a non-trivial source of bias in cross-sectional studies that examine the relationship between duration of residence and health; future studies should use methods that assess arrival cohort effects. Considering the changing tobacco contexts in immigrants’ origin countries, smoking prevention and cessation interventions should take into account not only time in the US, but also the period during which immigrant cohorts arrived in the US, as well as the smoking trends in immigrants’ origin countries [34,35,36], particularly at the time the immigrant cohort left. For instance, if an immigrant arrives in the U.S. at a time when smoking is already low, the decrease in smoking may be lower in magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, findings speak to the importance of global tobacco control surveillance and policy. Monitoring changes in tobacco prevalence in Latin American immigrant sending countries might improve our ability to anticipate smoking trends among newly arrived cohorts of immigrants [36]. Finally, studies of immigrant health should consider how immigrant arrival cohorts vary based on dynamic origin country contexts.…”
Section: Discussionmentioning
confidence: 99%
“…9 Prior research suggests that immigrants are less likely to use tobacco than persons born within the United States. [10][11][12] For instance, a recent national study showed that US-born Mexican-Americans had 1.5 times higher odds of being current smokers than recent immigrants with less than 10-year residency in the United States, which indicates that their origin culture might have a protective effect on smoking. 12 Acculturation describes the process of immigrants maintaining their original culture while developing relationships with the new culture of their host country, resulting in changes in health beliefs and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For instance, a recent national study showed that US-born Mexican-Americans had 1.5 times higher odds of being current smokers than recent immigrants with less than 10-year residency in the United States, which indicates that their origin culture might have a protective effect on smoking. 12 Acculturation describes the process of immigrants maintaining their original culture while developing relationships with the new culture of their host country, resulting in changes in health beliefs and behaviors. 13 The relationship between smoking tobacco and acculturation, often measured by proxies such as duration in the United States and language proficiency, varies by race/ethnicity and sex.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence has shown that the intensity of health selection might change over time. Previous studies in Mexico and the U.S. found that smoking selectivity increased among women because of changes in Mexico’s tobacco control policies [29]. Another study found increased health selection of obesity as the Mexican obesity prevalence increased [30].…”
Section: Introductionmentioning
confidence: 99%